Analysis of critical constraint factors affecting the performance of Transportation projects - Sowmmiya Narayanan S; Deepalakshmi S; Surya Raj Kumar (International Journal of Urban Design and Development, 2023)
Infrastructure is a country's biggest source of economic growth, which is made up of a variety of facilities and processes. It includes all the amenities and services required for urbanization, economic expansion, improved quality of life, and thriving companies. Transportation is one of the most important industries for any nation's economy, but constraints exist in all working environments. A construction constraint is a condition that makes it difficult to achieve the goals of a project. The aim and scope of this study are to identify the constraints of transportation projects. It is critical to recognize potential constraints that may arise throughout the course of a project, but this will help to avoid wasting resources and avoiding delays caused by poor planning. Therefore, managing the constraints is necessary for the project to function well and also escalates the limpidity of project management. Constraints occurring during the construction stage also have a greater impact, equivalent to the constraint factors occurring during the preconstruction stage. The constraint factors are classified based on these categories and compared to identify the constraint factor which creates more impact on both the stages and eliminates them.
Keywords: Transport infrastructure; bridges; constraints; metro; ranking; roads